2002
DOI: 10.1007/s10350-004-6333-7
|View full text |Cite
|
Sign up to set email alerts
|

Defunctioning Stoma in Low Anterior Resection With Colonic Pouch for Rectal Cancer

Abstract: This study suggests that the routine use of diversion does not protect the patient from anastomotic complications or pelvic sepsis and its use requires a second admission for closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 21 publications
1
47
1
2
Order By: Relevance
“…The clinical leakage rate of 8.2% reported in this present study is similar to that reported in other larger series (sample size >300 cases) [14,15,16], but relatively lower than that reported in previous studies without a protective stoma [3, 4, 12, 13]. The findings of the present study may be attributed to the fact that some studies without a protective stoma included only extraperitoneal anastomosis, while tension-free anastomosis was strictly performed in the present study by means of complete mobilization of splenic flexure, proximal ligation of inferior mesenteric vessels and no coloplasty or colonic pouch formation.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The clinical leakage rate of 8.2% reported in this present study is similar to that reported in other larger series (sample size >300 cases) [14,15,16], but relatively lower than that reported in previous studies without a protective stoma [3, 4, 12, 13]. The findings of the present study may be attributed to the fact that some studies without a protective stoma included only extraperitoneal anastomosis, while tension-free anastomosis was strictly performed in the present study by means of complete mobilization of splenic flexure, proximal ligation of inferior mesenteric vessels and no coloplasty or colonic pouch formation.…”
Section: Discussionsupporting
confidence: 76%
“…However, other investigators [4, 5] failed to show the advantage of protective stoma on the reoperation rate in patients with anastomotic leakage and no published studies [3, 21] have demonstrated the benefit of protective stoma on mortality rate after leakage. Considering that one-fifth of the temporary stoma might never be reversed [6] and that stomal closure is associated with 3% mortality and 20% morbidity [25], surgeons should deliberate over a decision to create a protective stoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The existing three studies, published in 1983, 1997, and 2003, were underpowered, with only 50, 38, and 36 patients included, respectively. 9Y11 Other prospective and retrospective studies had indifferent conclusions, some reporting no differences for mortality and morbidity, 9,12,13 others favored a protective ileostomy caused by a decrease of symptomatic anastomotic failures. 14Y17 Therefore, a large, randomized, controlled trial was believed to be overdue to investigate the benefit of a diverting ileostomy.…”
mentioning
confidence: 99%